2019
DOI: 10.1002/ecs2.2717
|View full text |Cite
|
Sign up to set email alerts
|

Insect and plant traits drive local and landscape effects on herbivory in grassland fragments

Abstract: Herbivory is one of the most important antagonistic insect–plant interactions and can be influenced by factors at local and landscape scales. Landscape fragmentation may reduce herbivory directly (i.e., decreasing abundance and species richness of herbivores), but also indirectly increase herbivory (i.e., releasing herbivores from top‐down control). At a local scale, reduced plant diversity may enhance herbivory through lessened associated resistance, while resource availability (i.e., higher vegetation height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
1
5
1
Order By: Relevance
“…well identified herbivore species (e.g.,Plath, Dorn, Riedel, Barriois, & Mody, 2012;Damien et al, 2016;Muiruri & Koricheva, 2016). Yet, the leaves may have accumulated mines made by several species, showing the same pattern of response to tree diversity as the diversity of herbivore guilds.Our results provide no supporting evidence to the effect of tree location at forest edge or interior on herbivore-plant interactions.This result confirms those recently found byvan Schrojenstein Lantman et al (2018) andRossetti, Verena, Videla, Tscharntke, and Batary (2019), but contradictsWirth et al (2008) andMaguire et al (2016) who showed that tree location can affect herbivory patterns. The only significant effect of tree diversity was observed on leaf miners in our study.…”
supporting
confidence: 89%
“…well identified herbivore species (e.g.,Plath, Dorn, Riedel, Barriois, & Mody, 2012;Damien et al, 2016;Muiruri & Koricheva, 2016). Yet, the leaves may have accumulated mines made by several species, showing the same pattern of response to tree diversity as the diversity of herbivore guilds.Our results provide no supporting evidence to the effect of tree location at forest edge or interior on herbivore-plant interactions.This result confirms those recently found byvan Schrojenstein Lantman et al (2018) andRossetti, Verena, Videla, Tscharntke, and Batary (2019), but contradictsWirth et al (2008) andMaguire et al (2016) who showed that tree location can affect herbivory patterns. The only significant effect of tree diversity was observed on leaf miners in our study.…”
supporting
confidence: 89%
“…Maximum vegetation height (VH) did not show any effect on any of these groups. This is not consistent with other studies where this structural feature was relevant for herbivores (Rossetti et al, 2019). In our system, this might be explained by the dominance of a tall grass invasive species (Sorghum halepense) on some edges.…”
Section: Discussioncontrasting
confidence: 99%
“…Land use data were obtained from the Ministry of Environment, Korea. Land use data were extracted for a 500 m radius of each collection site [16,32,33] using GIS software (version 10.1, ArcGIS, Redlands, CA, United States), and these data were used to calculate the proportion (%) of each land use. To avoid issues with GIS, distances that covered the largest area of a particular region were used, and the GPS coordinates were used as the site of origin to minimize potential errors caused by the GIS process.…”
Section: Methodsmentioning
confidence: 99%